Meningkatkan Keterampilan Sosial Dan Hasil Belajar Siswa Dalam Mata Pelajaran Pendidikan Pancasila Menggunakan Model Penguin Pada Siswa Kelas V SDN Gandaria 2 Barito Kuala - Sartika, Sartika; Hidayat, Ari (CV. ITTC INDONESIA, 2024)
The problem in this research is the low level of social skills and student learning outcomes. This is due to a lack of development of social skills in children, the influence of an unsupportive surrounding environment, limitations in communication or self-expression. An effort to overcome this problem is to apply the PENGUIN learning model. Yes, it is a combination model of Problem based learning, Number heads together, Role playing. The aim of this research is to determine teacher activities, students' social skills and to improve learning outcomes. This research used a classroom action research (PTK) approach, which was carried out in four meetings. The types of data in this research are qualitative and quantitative data. Qualitative data was obtained through observing teacher activities. Qualitative and quantitative data for students' social skills and student learning outcomes obtained through measurement techniques using group and individual written tests. The research subjects were class V students, even semester, SDN Gandaria 2, academic year 2023/2024. The results of this research show that the teacher's activities at meeting I achieved fairly good criteria, meeting II achieved good criteria, meeting three achieved good criteria and meeting four achieved good criteria. Students' social skills at meeting I reached 33% which increased at meeting II reaching 50% at meeting III reaching a percentage of 75% and experienced a very good increase at meeting IV reaching a percentage of 100%. Student learning outcomes at meeting I reached 42% which increased at meeting II reaching 50% at meeting III reaching a percentage of 83% and experienced a very good increase at meeting IV reaching a percentage of 100%. Based on these findings, it can be concluded that the PENGUIN model can improve students' social skills and learning outcomes.